HUBUNGAN PENGETAHUAN DAN EFIKASI DIRI PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Mailani, Fitri (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Background: Good knowledge will help patients with chronic kidney disease undergoing hemodialysis have good efikasi diri to overcome the symptoms and complaints experienced to improve their quality of life. This study aimed to determine the knowledge and efikasi diri of chronic kidney disease patients undergoing hemodialysis and the relationship. Method: This study is a descriptive correlational study in which 131 chronic kidney disease patients undergoing hemodialysis in Padang City became research respondents. The study was conducted in two hemodialysis units in the city of Padang, namely, the hospital. M. Jamil Padang and Tk III Hospital Reksodiwiryo. The sampling technique was purposive sampling, taking into account the inclusion criteria. The study was conducted in April 2022. Spearman correlation test was used to see the relationship between knowledge and efikasi diri of chronic kidney disease patients undergoing hemodialysis. Result: The results showed that the average value of knowledge of patients undergoing hemodialysis was 17.94 (2,968) (range 0-25), and the average value of efikasi diri was 43.57 (9.89) (range 6-60). The correlation test results showed a significant positive relationship between education and efikasi diri with a p-value of 0.000 (p <0.05). Conclusion: It is expected that health workers have a structured educational program to increase knowledge of chronic kidney disease patients undergoing hemodialysis so that patients can increase efikasi diri in overcoming the symptoms they feel.